DEPICTION OF INDIAN SOCIETY BY CONTEMPORARY WATERCOLOR ARTISTS - Bala, Rajni; Viranjan, Ram (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Art is a mirror that reflects our thoughts, emotions, ideas, and desires hence reflects the society we live in. It is a medium that expresses the wide range of human activities via creative and imaginative talents. Since art operates on imagination, it therefore allows diverse ways of considering life. Because the art has capability to communicate, the artist therefore creates it to fulfill his social responsibilities. Art has always been an integral and inseparable source of inspiration for existing society. Reflecting the exceptional features and collective tales of communities, the Indian folk paintings are a network for India’s rich past and diverse traditions. Indian art is filled with traditional history and is devotional in nature. Indian artists have chosen numerous measures for the evolution of their art. These artists employ various notions for same, they choose for numerous methods to bring their imagination to life; watercolor painting is one such method, where the pigments are mixed with water. The watercolor painting is acknowledged for its inherent delicacy and subtlety as this watercolor art is all about thin washes and transparent color. The present research is an attempt to study the relationship between art and society which are often considered as two faces of the same coin. Furthermore, it strives to explore Abanindranath Tagore, Gaganendranath Tagore, Ganesh Pyne, Vasudeo Kamth, Samir Mondal, Rajkumar Sthabathy, Ram Jaiswal, Raghunath Sahu, and many others’ contributions in watercolor painting. To gain deep understanding, the study is designed with the qualitative approach, that utilizes both primary and secondary data. Furthermore, being explorative in nature the study focuses on firsthand experience with the contemporary watercolor artists such as Ram Jaiswal (personal interview), Bijay Biswal (personal interview) and Raghunath sahu (telephonic interview) to seek their contributions in the watercolor painting